LITERASI WISATA PENDIDIKAN: UPAYA PENINGKATAN PARTISIPASI MASYARAKAT DALAM PENDIDIKAN SERTA PEMERTAHANAN BAHASA DAERAH DAN KEARIFAN LOKAL - Muhammad Thohri; Marham Jupri Hadi; Bukhori Muslim (JURNALISTRENDI : JURNAL LINGUISTIK, SASTRA, DAN PENDIDIKAN, 2021)
Traveling is a human need and travel activities will continue to be done throughout our lives. But the existence of pandemic covid 19 has a tremendous impact on the country's tourism industry which triggers the emergence of unemployment. One alternative to recovery is to generate Rural Tourism, namely by the implementation of the Education Tourism model, or WIKAN. Wikan is one of the rural tourism development strategies that are expected to be able to become a medium of tourism education, especially to people who are in tourist destinations. This article will introduce about the concept of educational tourism, the urgency of its implementation, some examples of good practices for the application of educational tourism at the international, national and local levels. In addition, some recommendations to develop educational tourism destinations to maintain regional languages and local wisdom are also the focus of this article.